2020
DOI: 10.1186/s12877-020-01838-8
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in hospitalized older patients with versus without prolonged use of opioid analgesics, benzodiazepines, and z-hypnotics: a cross-sectional study

Abstract: Background Central nervous system depressant medications (CNSDs) such as opioid analgesics and sedative-hypnotics are commonly prescribed to older patients for the treatment of chronic pain, anxiety and insomnia. Yet, while many studies reported potential harms, it remains unknown whether persistent use of these medications is beneficial for older patients’ self-reported health-related quality of life (HRQoL). The present study clarified this knowledge gap through comparing HRQoL of hospitalized older patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…Además, esta puntuación también ha sido inferior en quienes mostraron ansiedad o insomnio a pesar del tratamiento. En una investigación reciente 32 los pacientes de edad avanzada hospitalizados con uso prolongado de benzodiacepinas informaron de una peor CVRS, comprobándose puntuaciones más bajas respecto a los pacientes no tratados tanto en el índice EQ como en EQ-EVA.…”
Section: Discussionunclassified
“…Además, esta puntuación también ha sido inferior en quienes mostraron ansiedad o insomnio a pesar del tratamiento. En una investigación reciente 32 los pacientes de edad avanzada hospitalizados con uso prolongado de benzodiacepinas informaron de una peor CVRS, comprobándose puntuaciones más bajas respecto a los pacientes no tratados tanto en el índice EQ como en EQ-EVA.…”
Section: Discussionunclassified
“…Limited evaluation of the use of hypnotics, such as benzodiazepines and Z‐drugs, in insomnia has failed to show any change in outcomes for HRQoL (Scalo et al., 2015). In other settings, high‐dose benzodiazepines have shown deleterious effects on HRQoL (Cheng et al., 2020; Tamburin et al., 2017). The associated improvement in HRQoL in this study is consistent with changes previously identified in a Canadian cohort who received medical cannabis for insomnia (Vaillancourt et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Limited evaluation of the use of hypnotics, such as benzodiazepines and Z-drugs, in insomnia has failed to show any change in outcomes for HRQoL (Scalo et al, 2015). In other settings, high-dose benzodiazepines have shown deleterious effects on HRQoL (Cheng et al, 2020;Tamburin et al, 2017).…”
Section: Adverse Eventmentioning
confidence: 99%
“…CRs for this group were high among all dose categories, including the reference category, and covariates included in models likely disproportionately affected older individuals. Older people prescribed higher opioid doses may also be less mobile due to the sedating effects of opioids or the conditions for which these doses are indicated; moderate to severe pain and opioid use are associated with reduced mobility in older adults, [50][51][52] potentially translating to fewer opportunities for falling.…”
Section: Discussionmentioning
confidence: 99%